2019
DOI: 10.1098/rsbl.2019.0349
|View full text |Cite
|
Sign up to set email alerts
|

Generalist birds outperform specialist sunbirds as pollinators of an AfricanAloe

Abstract: Bird pollination systems are dominated by specialist nectarivores, such as hummingbirds in the Americas and sunbirds in Africa. Opportunistic (generalist) avian nectarivores such as orioles, weavers and bulbuls have also been implicated as plant pollinators, but their effectiveness as agents of pollen transfer is poorly known. Here, we compare the single-visit effectiveness of specialist and opportunistic avian nectarivores as pollinators of Aloe ferox, a plant that relies almost exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…We found that learning did not make E. multifasciata consume fewer bitter crickets but changed their foraging sequence and priority; with more information on the color-taste coupling of the prey, E. multifasciata targeted and consumed palatable prey with higher priorities, regardless of their boldness (Figures 4A-F, brown vs. blue curves). This underscored the flexible and opportunistic foraging habits of E. multifasciata , which was commonly observed in other generalist predators (e.g., Terraube and Arroyo 2011; Diller et al 2019). In the field, the presence of high-quality prey is likely staggered and unpredictable.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We found that learning did not make E. multifasciata consume fewer bitter crickets but changed their foraging sequence and priority; with more information on the color-taste coupling of the prey, E. multifasciata targeted and consumed palatable prey with higher priorities, regardless of their boldness (Figures 4A-F, brown vs. blue curves). This underscored the flexible and opportunistic foraging habits of E. multifasciata , which was commonly observed in other generalist predators (e.g., Terraube and Arroyo 2011; Diller et al 2019). In the field, the presence of high-quality prey is likely staggered and unpredictable.…”
Section: Discussionmentioning
confidence: 56%
“…The copyright holder for this preprint this version posted December 13, 2022. ; https://doi.org/10.1101/2022.12.13.520202 doi: bioRxiv preprint (e.g., Terraube and Arroyo 2011;Diller et al 2019). In the field, the presence of high-quality prey is likely staggered and unpredictable.…”
Section: Avoidance Learning Reduces Variation In Foraging Behaviormentioning
confidence: 99%
“…Indeed, plants are often visited by a myriad of different functional pollinators groups and this can make it difficult to determine whether there has been functional specialization of flowers to a particular group. In these cases, data on the relative pollination importance of different visitor groups are essential to resolve the degree of specialization in a pollination system (Aigner, 2005; Diller et al., 2019; Johnson & Steiner, 2000; Wester & Johnson, 2017; Wilson, 1995). The importance of a given visitor group in a mutualism is a function of the number of visits and the amount of pollen deposited per visit (Schupp et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…scutellata Lepeletier) to seed set of the self‐incompatible South African treelet Aloe ferox Mill. This species produces numerous flowers that are attractive to both native honeybees and several bird species (Hoffman, 1988; Diller et al, 2019). Honeybees are far more frequent than birds as visitors to flowers of A. ferox (Hoffman, 1988; Hargreaves et al, 2012) and deposit pollen on stigmas (Diller et al, 2019), yet bird exclusion experiments indicate that honeybees are very poor pollinators when compared to birds, as assessed by resulting seed set (Strokes and Yeaton, 1995; Botes et al, 2009; Hargreaves et al, 2012).…”
mentioning
confidence: 99%
“…This species produces numerous flowers that are attractive to both native honeybees and several bird species (Hoffman, 1988; Diller et al, 2019). Honeybees are far more frequent than birds as visitors to flowers of A. ferox (Hoffman, 1988; Hargreaves et al, 2012) and deposit pollen on stigmas (Diller et al, 2019), yet bird exclusion experiments indicate that honeybees are very poor pollinators when compared to birds, as assessed by resulting seed set (Strokes and Yeaton, 1995; Botes et al, 2009; Hargreaves et al, 2012). This is consistent with studies of many other aloes, which have also shown that honeybees make little contribution to seed set in comparison to birds, despite being frequent visitors (Botes et al, 2009; Hargreaves et al, 2010, 2012; Duffy et al, 2021, but see Patrick et al, 2018; Duffy et al, 2020).…”
mentioning
confidence: 99%